Rational bubbles and fractional integration - Robinson Kruse (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
In this article we provide evidence for a rational bubble in S&P 500 stock prices by applying a test for changing persistence under fractional integration proposed by Sibbertsen and Kruse (2007). We find strong evidence for stationary long memory before the estimated change point in 1955 and a unit root afterwards. These results bring two empirical findings in line: on one hand they confirm the previous result of fractional integration and on the other hand they support the hypothesis of a rational bubble.
Keywords: C12; C22; G12; 330; Fractional integration; bubbles; changing persistence; Börsenkurs; Bubbles; Rationales Verhalten; Zeitreihenanalyse; Strukturbruch; Statistischer Test; Großbritannien